“Damocles shadowing”: An innovation in the second phase of EMU - Heinrich Matthes (Intereconomics, 1994)
Since the widening of the fluctuation bands in the European Monetary System in 1993 the previous core countries have pursued a “D-Mark shadowing”. The characteristic feature of this shadowing is the participating countries' willingness to voluntarily return to, and maintain, the old exchange rate parities. Our author analyses this process and its consequences for the planned monetary union.
Keywords: 330; European Monetary System